D‐dopachrome tautomerase in cardiovascular and inflammatory diseases—A new kid on the block or just another MIF?. Issue 11 (21st October 2022) - Zan, Chunfang; Yang, Bishan; Brandhofer, Markus; El Bounkari, Omar; Bernhagen, Jürgen
Abstract: Macrophage migration inhibitory factor (MIF) as well as its more recently described structural homolog D‐dopachrome tautomerase (D‐DT), now also termed MIF‐2, are atypical cytokines and chemokines with key roles in host immunity. They also have an important pathogenic role in acute and chronic inflammatory conditions, cardiovascular diseases, lung diseases, adipose tissue inflammation, and cancer. Although our mechanistic understanding of MIF‐2 is relatively limited compared to the extensive body of evidence available for MIF, emerging data suggests that MIF‐2 is not only a functional phenocopy of MIF, but may have differential or even oppositional activities, depending on the disease and context. In this review, we summarize and discuss the similarities and differences between MIF and MIF‐2, with a focus on their structures, receptors, signaling pathways, and their roles in diseases. While mainly covering the roles of the MIF homologs in cardiovascular, inflammatory, autoimmune, and metabolic diseases, we also discuss their involvement in cancer, sepsis, and chronic obstructive lung disease (COPD). A particular emphasis is laid upon potential mechanistic explanations for synergistic or cooperative activities of the MIF homologs in cancer, myocardial diseases, and COPD as opposed to emerging disparate or antagonistic activities in adipose tissue inflammation, metabolic diseases, and atherosclerosis. Lastly, we discuss potential future opportunities of jointly targeting MIF and MIF‐2 in certain diseases, whereas precision targeting of only one homolog might be preferable in other conditions. Together, this article provides an update of the mechanisms and future therapeutic avenues of human MIF proteins with a focus on their emerging, surprisingly disparate activities, suggesting that MIF‐2 displays a variety of activities that are distinct from those of MIF.